Sleep disorders as a public health problem - Lau, Karolina; Jośko, Jadwiga (Polish Journal of Public Health, 2010)
Sleep disorders are alongside civilization diseases, tobacco smoking, alcohol drinking, obesity, and low physical activity, one of the most frequent factors leading to health problems. In Poland, likewise in other European countries, sleeping disorders concern over twenty percent of the country population. The most frequent sleep disorder is insomnia, which stands for about forty percent of all disorders. Less common, however equally dangerous in results, is Obstructive Sleep Apnea and narcolepsy. Moreover, numerous data indicate, that quantitative or qualitative sleep disorders can increase the risk of depression, diabetes, arterial hypertension and difficulties with maintaining the correct body mass index (BMI). The important indicator is also the health-related quality of life (HRQL) that decreases significantly in people who sleep too short. The fact that a mere 1/3 of people declaring sleep disorders consult them with their doctor is alarming. Such attitude of the patients is today, alongside the doctors’ incorrect diagnostic procedure, the main reason for the inefficiency of the struggle with the problem. Thus incredibly important seems to be the role of public health sector, taking appropriate actions as far as prevention, education, screening and/or periodical investigations relating to sleep are concerned. Also hygiene and correct sleeping habits cannot be neglected. Such actions should be directed especially at groups of increased risk of sleep disorders.